Enhancing Conceptual Understanding of the Solar System Through 3D Augmented Reality in Primary Education - Eva Febyliana; Teuku Zaine Abror Attolok; Diaz Aditya; Raina Artika Ramadlonia; Taufik Ismail; Muhammad Zainudin Al Amin (Journal of Computing and Smart Ecosystems, 2025)
The advancement of digital technologies has introduced new methods in science education, including the use of Augmented Reality (AR). Traditional astronomy instruction often relies on two-dimensional media, which limits students’ ability to visualize and interact with celestial phenomena. This paper presents EduPlanet, a 3D AR-based educational application designed to enhance students’ understanding of the solar system. The application allows users to explore planets interactively, visualize orbital movements, and access informative content in real time. Developed using Unity and Vuforia SDK, EduPlanet consists of three main modules: learning content, marker-based AR visualization, and a quiz system with instant feedback. Functional testing using the Black Box method confirmed that all features performed as intended. Informal usability testing with elementary school students showed high levels of engagement, particularly in the AR and quiz components. The findings suggest that EduPlanet offers an effective and accessible tool to support astronomy learning in primary education, with potential for broader application in digital science pedagogy.